2016
DOI: 10.3892/or.2016.5328
|View full text |Cite
|
Sign up to set email alerts
|

Regorafenib induces extrinsic and intrinsic apoptosis through inhibition of ERK/NF-κB activation in hepatocellular carcinoma cells

Abstract: The aim of the present study was to investigate the role of NF-κB inactivation in regorafenib-induced apoptosis in human hepatocellular carcinoma SK-HEP-1 cells. SK-HEP-1 cells were treated with different concentrations of the NF-κB inhibitor 4-N-[2-(4-phenoxyphenyl)ethyl]quinazoline-4,6-diamine (QNZ) or regorafenib for different periods. The effects of QNZ and regorafenib on cell viability, expression of NF-κB-modulated anti-apoptotic proteins and apoptotic pathways were analyzed by the 3-(4,5-dimethylthiazol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
67
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(72 citation statements)
references
References 26 publications
4
67
1
Order By: Relevance
“…DMSO was finally used to dissolve the insoluble purple formazan product into a colored solution and then prepared for measurement. The absorbance of this colored solution can be quantified by measuring at a certain wavelength (570 nm) by a spectrophotometer (Tecan Group Ltd., Männedorf, Switzerland) …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…DMSO was finally used to dissolve the insoluble purple formazan product into a colored solution and then prepared for measurement. The absorbance of this colored solution can be quantified by measuring at a certain wavelength (570 nm) by a spectrophotometer (Tecan Group Ltd., Männedorf, Switzerland) …”
Section: Methodsmentioning
confidence: 99%
“…Cells were transfected with NF‐κB luciferase reporter plasmid (pNF‐κB/ luc2 ) (Promega, Madison, WI, USA) by jetPEI transfection reagent (Illkirch, Bas‐Rhin, France) and then selected with 200 μg/mL of hygromycin B for 2 weeks as described previously. Stable clones which constitutively express function of NF‐κB reporter gene were rename as TSGH/NF‐κB‐ luc2 cells and used for NF‐κB reporter gene assay . For NF‐κB luciferase assay, 3 × 10 4 TSGH/NF‐κB‐ luc2 cells were seeded in 96 wells overnight before regorafenib (0–40 μM) or different inhibitor (0.5 μM NF‐κB inhibitor, 10 μM ERK inhibitor, 10 μM p38 inhibitor, 10 μM AKT inhibitor, 10 μM JNK inhibitor) treatment for 48 h. Luciferase reagent, d ‐luciferin solution (500 μM d ‐luciferin in 100 μL PBS), was added into each well for 10 min incubation.…”
Section: Methodsmentioning
confidence: 99%
“…High expression of NF-ĸB contributes tumor progression and modulates acquired resistance to treatment in glioblastoma (20). TMZ not only induces apoptosis but also triggers NF-ĸB activity in glioblastoma cells.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies on HCC cell lines, such as SKHep1 and Huh7, we found that inhibition of NF-ĸB activation impairs tumor progression including antiapoptosis, angiogenesis, proliferation, and metastasis. In addition, blockage of ERK activation may also downregulate NF-ĸB-modulated tumor progression (5,7).…”
Section: Discussionmentioning
confidence: 99%
“…Active NF-ĸB promotes tumor growth, antiapoptosis, angiogenesis, and metastasis of HCC through overexpression of tumor progression-associated proteins encoded by NF-ĸB-targeted genes (4)(5). The MAPK cascade has been shown to activate NF-ĸB-modulated tumor progression in various cancer cells.…”
mentioning
confidence: 99%